Penalaran dalam Media Lokal: Analisis Opini Pada Kabar Madura - Jannatul Firdaus; Ria Kasanova (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to analyse reasoning in the opinion columns of Kabar Madura, a prominent local newspaper in Madura. The research employs a qualitative approach with a descriptive-analytical design to understand and evaluate the quality of argumentation in these opinion columns. Data were collected through content analysis and discourse analysis of opinion articles published within a specific timeframe. The findings reveal that while many articles demonstrate effective rhetorical use and a critical approach, there are deficiencies in evidence presentation and logical consistency. More experienced writers tend to construct stronger arguments supported by relevant evidence, whereas less experienced writers often struggle to formulate coherent and logical arguments. This variation in argumentative quality indicates a need for writer training and capacity development. Additionally, the analysis shows that some articles adopt a critical approach that aids readers in understanding the complexities of local issues. The local social and cultural context also influences reasoning in the opinion columns, with articles relevant to the daily lives of the Madurese community receiving more positive responses. The study concludes that enhancing reasoning quality in opinion columns can improve the credibility and impact of local media in shaping public opinion. Practical recommendations include providing training for writers and further research encompassing more local media and mixed methods for more comprehensive results. This research contributes significantly to the development of more critical and responsible journalism within the local media context in Indonesia.